Manganese catalyzed α-methylation of ketones with methanol as a C1 source. Issue 3 (10th December 2018) - Bruneau-Voisine, Antoine; Pallova, Lenka; Bastin, Stéphanie; César, Vincent; Sortais, Jean-Baptiste
Abstract : The direct α-methylation of ketones with methanol under hydrogen borrowing conditions using a well-defined manganese PN 3 P pre-catalyst was, for the first time, achieved. Abstract : The direct α-methylation of ketones with methanol under hydrogen borrowing conditions using a well-defined manganese PN 3 P complex as a pre-catalyst was, for the first time, achieved. The reactions typically proceed at 120 °C for 20 h with 3 mol% pre-catalyst loading and in the presence of NaO t Bu (50 mol%) as base. The scope of the reaction was extended to the α-methylation of esters.